Chitosan oligosaccharide based hydrogel: An insight into the mechanical, drug delivery, and antimicrobial studies - Mallick S.P.; Panda S.P.; Gayatri A.; Kunaal Y.; Naresh C.; Suman D.K.; Samineni J.; Siddiqui N.; Singh B.N. (My University, 2025)
Hydrogel is a macromolecular polymer gel constructed of a network of cross-linked polymer chains. Chitosan oligosaccharide (CO) is a natural polymer that has an efficient biodegradability and is used to prepare hydrogels for efficient drug delivery. CO is combined with Carboxy Methyl Cellulose (CMC) to produce a hydrogel in different compositions for the best suitable option where the drug delivery and biocompatibility are most efficient. The chemical hydrogels of the composition CO and CMC were prepared by adding the cross-linker mixture of glutaraldehyde, alcohol, and distilled water. After the hydrogels were prepared, it is subjected to a series of tests, i.e., microscopy, hemocompatibility, mechanical strength, impedance measurement, drug release, antimicrobial activity. Ccross-linking is achieved by adding a mixture of glutaraldehyde, alcohol, and distilled water. Thus, the best composition of the mixture of the two compounds – Chitosan oligosaccharide and the Carboxy Methyl Cellulose is determined and used for efficient drug delivery. © 2020 by the authors.